(untitled) (Research, Society and Development, 2021)
This article is an excerpt from doctoral research and aims, exclusively for that text, to reflect on what my (auto)biographical writings revealed, in training memorials built throughout life, as to becoming a teacher, teacher trainer, researcher and the reflections of these life paths, personal and professional, do not constitute the research puzzle. In this sense, therefore, authors who discuss this research perspective are part of the theoretical foundation, such as, for example, Clandinin (2013), Clandinin and Connely (2015), Josso (2007), Souza (2006), Benjamin (1996), Larrosa Bondía (2002), Roldão (2007), Flores (2014), D’Ambrosio (1998) and Passos (2010). Throughout my personal and professional trajectory, as it was presented throughout the article, I was deeply involved with the issues of playfulness and teacher training that teach (Aaron) mathematics. All of this brought me closer to the PhD research puzzle. I hope that this text will allow readers to get closer to narrative research and that more studies of this nature will be built in Brazil.